If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -1) + 3(3 + -2x) = 0 Reorder the terms: 2(-1 + 4x) + 3(3 + -2x) = 0 (-1 * 2 + 4x * 2) + 3(3 + -2x) = 0 (-2 + 8x) + 3(3 + -2x) = 0 -2 + 8x + (3 * 3 + -2x * 3) = 0 -2 + 8x + (9 + -6x) = 0 Reorder the terms: -2 + 9 + 8x + -6x = 0 Combine like terms: -2 + 9 = 7 7 + 8x + -6x = 0 Combine like terms: 8x + -6x = 2x 7 + 2x = 0 Solving 7 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| n+3=5n | | -132.6x(-53.78)= | | (2+c)=5(2+c)-6(2+c) | | -2(y)+2.82(-5)=24 | | 4a+3-a=7+2+a | | (2x+1)=(4x-3) | | 4(x-1)=6x | | y=-1000x^2+1100x-2.5 | | 4(6-6)=8 | | 4(x-4)=6x | | 3(-1-2)+6(2-4)= | | 9x-6=102 | | 5(x-2)=3(x-3) | | 5(y-4)/3=2y-5 | | 2(x+9)=24 | | 2.22m=4.4 | | -17=0.20n-20 | | -5(b+3)=-7b-1 | | x+25=-3(x-7) | | Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 | | 9a=25b | | 8x-11=13x+15 | | 8.1-y=20 | | 18-x=(11+x)+3 |